Evaluation of the analgesic effect of high-cannabidiol-content cannabis extracts in different pain models by using polymeric micelles as vehicles (2023)
ABSTRACT: Currently, cannabis is considered an attractive option for the treatment of various diseases, including pain management. Thus, developing new analgesics is paramount for improving the health of people suffering from chronic pain. Safer natural derivatives such as cannabidiol (CBD) have shown excellent potential for the treatment of these diseases. This study aimed to evaluate the analgesic effect of a CBD-rich cannabis extract (CE) encapsulated in polymeric micelles (CBD/PMs) using different pain models. The PEG-PCL polymers were characterized by gel permeation chromatography and 1H-NMR spectroscopy. PMs were prepared by solvent evaporation and characterized by dynamic light scattering (DLS) and transmission electron microscopy. The analgesic activity of CBD/PMs and nonencapsulated CE rich in CBD (CE/CBD) was evaluated using mouse thermal, chemical, and mechanical pain models. The acute toxicity of the encapsulated CE was determined by oral administration in mice at a dose of 20 mg/kg for 14 days. The release of CBD from the nanoparticles was assessed in vitro using a dialysis experiment. CBD/PMs with an average hydrodynamic diameter of 63.8 nm obtained from a biocompatible polyethylene glycol-block-polycaprolactone copolymer were used as nanocarriers for the extract formulations with 9.2% CBD content, which corresponded with a high encapsulation efficiency of 99.9%. The results of the pharmacological assays indicated that orally administered CBD/PMs were safe and exerted a better analgesic effect than CE/CBD. The micelle formulation had a significant analgesic effect in a chemical pain model, reaching a percentage of analgesia of 42%. CE was successfully encapsulated in a nanocarrier, providing better stability. Moreover, it proved to be more efficient as a carrier for CBD release. The analgesic activity of CBD/PMs was higher than that of free CE, implying that encapsulation is an efficient strategy for improving stability and functionality. In conclusion, CBD/PMs could be promising therapeutics for pain management in the future.